COMMUNITY EMPOWERMENT THROUGH VILLAGE TOURISM DEVELOPMENT AND ITS IMPLICATIONS FOR REGIONAL SOCIO-CULTURAL RESILIENCE - Haloho, Edward; Meka, Ardiles Hasianta; Khafilwara, Febby; Limbong, Gusti Elcitra (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Ecotourism development has been regulated and established by the central government through (Minister of Home Affairs Regulation) Number 33 of 2009 regarding Guidelines for Ecotourism Development in regions. These guidelines discuss the principles of ecotourism development in local areas. Ecotourism is a form of responsible nature tourism that emphasizes education, understanding, and support for conservation efforts, as well as the improvement of local community income Minister of Home Affairs Regulation Number 33 of 2009, Article 1. Ecotourism is a popular form of tourism among travelers (Sugiarti, 2015). Ecotourism development includes planning, utilization, and control activities. According to UNESCO (2009) and Wood (2002:14), there are five (5) fundamental principles of ecotourism development in Indonesia: conservation, education, tourism, economy, and community participation.